Language is the key : a Canadian Language Benchmarks model - Jezak, Monika, 1962- (University of Ottawa Press, 2017)
"The development of the Canadian Language Benchmarks (CLB) and their French equivalent, Niveaux de compétence linguistique canadiens (NCLC)--scales representing the levels of learner language proficiency--gave rise to the widely recognized system of official language training for adult immigrants to Canada. Language is the Key offers an examination of this leading language training model. The CLB/NCLC success was dependent on many factors--outstanding work by leading Canadian scholars; steady commitment of the government and non-governmental stakeholders at the federal, provincial, and local level; and, last but not least, unconditional commitment and caring on the part of an invested community of practice. Language is the key covers a range of topics: historical and political context that lead to the development of the Canadian standards, their current positioning in global educational markets, as well as their research and teaching cultures. This edited volume provides a comprehensive overview of recent and ongoing projects and of CLB- and NCLC-related materials, tools and resources for teaching and assessment. Finally, it offers a bold outlook, proposing various scenarios to branch out beyond these benchmarks into the domains of higher education, essential skills, literacy, workplace training, as well as international and Indigenous languages. The 20th anniversary of the CLB/NCLC provides an opportunity to reflect on the scope and importance of this exceptional Canadian intellectual product."--